Coexistence of P190 BCR/ABL transcript and CALR 52-bp deletion in chronic myeloid leukemia blast crisis: a case report - najmaldin saki; Mohammad Seghatoleslami; Neda Ketabchi; Alireza Ordo; Javad Mohammadi-Asl; Neda Golchin (Mediterranean Journal of Hematology and Infectious Diseases)
We present a case of a 78-year-old woman presented with thrombocytosis and high blast count, who had a history of splenectomy. Her cytogenetic analysis revealed aberrant chromosomal rearrangements in different clonal populations harboring 46XX karyotype with t(9;22)(q34;q11). RT-PCR assay detected the e1a2 BCR-ABL translocation resulting from a rearrangement of the minor breakpoint cluster region (m-bcr) in the BCR gene. Subsequent evaluations of the disease showed calreticulin (CALR) 52-bp deletion as well as the absence of JAK2V617F heterozygous mutation in granulocyte population of peripheral blood using allele-specific PCR and bi-directional DNA sequencing. To our knowledge, this is the first case of a patient initially diagnosed as p190 BCR-ABL transcript positive CML in blastic crisis characterized with a 52-bp deletion in CALR gene.